Problems faced by the sub-assistant agriculture officers (SAAOs) working in department of agricultural extension - Hamid, Md Imran; Datta, Susmita; Islam, Md Matiul (Research in Agriculture Livestock and Fisheries, 2020)
The overall agricultural development of Bangladesh is rapidly progressing. The advancement in agricultural attainments is not a problem free venture. Various new problems are being faced by the SAAOs (Sub-Assistant Agriculture Officers) at present. Thus the purpose of this study was to determine the extent of the problems faced by the SAAOs regarding agricultural extension at field level and to explore the relationships between the selected characteristics of the SAAOs and the faced problems. A number of 46 problems of SAAOs were selected as the focus issue (dependent variable). The study was conducted in Batiaghata and Dumuria upazila under Khulna district. Data were collected from randomly selected 53.97% of the SAAOs (34 out of 63) from each upazila, using an interview schedule during July10 to September 25 of 2019. A problem severity index (PSI) was used to make comparison among the 46 selected problems. Spearman’s Rank Order Correlation Coefficient (ρ) was used to ascertain the relationship between the focus issue (ordinal type of data) and personal characteristics of the respondents. In Batiaghata upazila about two-third of the SAAOs (61.5%) had moderate problems where, “slow rate of promotion compares to other govt. job”, “difficulties of getting promotion” and “shortage of manpower” ranked 1st, 2nd and 3rd position, respectively. In Dumuria upazila majority of the SAAOs (71.4%) had moderate problems where, “every block covers large area”, “shortage of manpower” and “difficulties of getting promotion” ranked 1st, 2nd and 3rd position, respectively. Student t-test result (t Stat 0.35; P(T<=t) two-tail 0.73) showed that there is no significant difference between the problems faced by the SAAOs of Dumuria and Batiaghata upazila. There was no significant relationship between extent of problems and selected characteristics in Batiaghata and Dumuria upazila, except job experience of SAAOs had showed a positive significant relationship. The SAAOs are facing various newly emerged problems at present while conducting agricultural extension activities which should be taken under consideration for priority based solution for sustainable agricultural advancement. Res. Agric., Livest. Fish.7(1): 61-73, April 2020